Desain dan Pengujian Mesin Sortasi Telur Ayam - Feby Nopriandi; Desrial .; Wawan Hermawan (PERTETA, 2015)
Based on Indonesian National Standard (SNI) No 3926:2008, egg weight is classified into three classifications: small (<50 g), medium (50-60 g), and large (>60 g). Nowadays egg grading process in Indonesia was still done manually. The objective of this research was for designing, constructing, and performance testing of egg sorting machine. The machine testing includes performance accuracy, machine capacity, and egg crack of the sorting result. The egg sorting machine consisted of five main parts: conveyor system, steering conveyor system, sorting conveyor system, and exit conveyor system. Test result showed that the machine could sort the egg with accuracy of 83 % without any cracking in eggshell. The machine capacity was most affected by the speed of sorting conveyor system. The variables which influence the speed of sorting conveyor system were initial speed rotation (Na), work speed rotation (Nb), and length of the track on initial speed rotation path (L). The maximum machine capacity was 61 eggs per minute and obtained by configuration of Na, Nb, and L of 15.5 rpm, 24.5 rpm, and 6 cm respectively.